Mouthwashes for the control of supragingival biofilm and gingivitis in orthodontic patients: evidence-based recommendations for clinicians - Alex Nogueira HAAS; Claudio Mendes PANNUTI; Ana Karina Pinto de ANDRADE; Elaine Cristina ESCOBAR; Eliete Rodrigues de ALMEIDA; Fernando Oliveira COSTA; José Roberto CORTELLI; Sheila Cavalca CORTELLI; Sigmar de Mello RODE; Vinicius PEDRAZZI; Rui Vicente OPPERMANN (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Properly performed daily mechanical biofilm control is the most important prevention strategy for periodontal diseases. However, proper mechanical biofilm control is not performed effectively by the majority of the population, mainly due to lack of motivation and of manual dexterity. Local biofilm retention factors may aggravate home oral hygiene quality. For this reason, patients wearing fixed orthodontic appliances comprise a group that may benefit from the daily use of mouthwashes. The purpose of this review was to perform a systematic search in the literature on antiseptics used to control supragingival biofilm and gingivitis in orthodontic patients. Six studies investigating the effect of chlorhexidine and 5 studies evaluating the effect of the daily use of antiseptics were found. Chlorhexidine showed better results in reducing plaque and gingivitis. However, because of its adverse effects after continuous use, it should not be indicated for long-term periods. Among the agents considered for daily use, the fixed combination of essential oils was the only one evaluated in a clinical trial, in which a comparative group presented a statistically significant clinical impact. There is no direct evidence supporting the indication of antiseptic agents for orthodontic patients other than chlorhexidine and essential oils. It can be concluded that, for patients undergoing orthodontic treatment, chlorhexidine should be considered for treating acute gingival inflammation, whereas essential oils should be indicated for long-term daily use in controlling supragingival biofilm.